The usage of financial services among Malaysian SMEs: an exploratory study - Humberto Ramirez; Thien Sang Lim (Social Sciences and Humanities Open, 2025)
The present qualitative investigation explores in depth the way in which financial services are utilized by SMEs in Malaysia. Financial services are economic packages utilized by SMEs in their routine financial operation. While prior research has reasonably documented the types of financial services used by SMEs, little is known about the precise mechanisms and decision-making processes of how those services are employed. An exploratory qualitative study was conducted to interview 13 SMEs owners in Sabah, Malaysia. Through connectivity and categorical analysis, the results derived 134 different codes and nine categorized themes, which reveal in detail managerial practices of how precisely financial services are put into the financial administration of SMEs. The findings have theoretical implications for the field of financial management. They constitute conceptual grounded insights that expand our understanding of how SMEs behave financially, and how those practices can directly improve their efficiency and performance. The results have also relevant implications for practice. SMEs managers can replicate the qualitative insights to improve their financial operation. Banks and policy makers can use the feedback from SMEs to improve the development of financial services. The categorized qualitative themes represent a starting point for future qualitative and quantitative research as potential constructs to amplify them and test their impact on SMEs performance.